New Horizons in the Pathogenesis, Pathophysiology and Treatment of Familial Hypercholesterolaemia - Viigimaa, Margus; Heinsar, Silver; Lovic, Dragan; Katsimardou, Alexandra; Piperidou, Alexia; Duishvili, Davit (Current Pharmaceutical Design, 2018)
Background: Familial Hypercholesterolaemia (FH) is an autosomal-dominant genetic disease and represents the most common genetic disorder: heterozygous 1/250 births, homozygous 1/300, 000 births. FH is characterized by high to very high low-density lipoprotein cholesterol (LDL-C), which is the main cause of increased incidence of premature atherosclerotic Cardiovascular Disease (CVD) or aortic stenosis. Objective: The aim of the review was to investigate the pathogenesis and the pathophysiology of FH. Results: The most common (60-80%) FH cause is mutations of the LDL Receptor (LDLR) protein (6 classes with a different number of receptors and functionality). Moreover, mutations in apolipoprotein B (APOB) (<5%) and gain-of-function mutations of proprotein convertase subtilisin/kexin type 9 genes (PCSK9) (<1%) contribute to its pathogenesis. An Autosomal Recessive Hypercholesterolaemia (ARH) is another cause, very rare (1/2.500 births), mainly in Sardinia. The remaining patients with a clinical diagnosis of monogenic hypercholesterolaemia do not present any known genetic cause. Since FH is a significant public health problem, early diagnosis and treatment are of utmost importance. Recent studies demonstrated the influence of the LDLR mutation type in the FH phenotype, associating a more severe clinical phenotype and worse advanced CVD in patients with null mutation than those with receptor-defective mutations. This analysis completes the adequate clinical diagnosis. Conclusion: Both homozygous and heterozygous FH are related to mutations of LDLR (mainly), APOB, PCSK9, while other rare forms exist. All aberrations lead to the impaired removal of LDL-C from the blood leading to its accumulation and subsequent CVD earlier than in the general population.
Keywords: Familial hypercholesterolaemia